2021
DOI: 10.3390/polym13132139
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Investigation on 3D Printing of Polyamide 11 and Thermoplastic Polyurethane via Multi Jet Fusion

Abstract: Multi Jet Fusion (MJF) is a recently developed polymeric powder bed fusion (PBF) additive manufacturing technique that has received considerable attention in the industrial and scientific community due to its ability to fabricate functional and complex polymeric parts efficiently. In this work, a systematic characterization of the physicochemical properties of MJF-certified polyamide 11 (PA11) and thermoplastic polyurethane (TPU) powder was conducted. The mechanical performance and print quality of the specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…This is confirmed by the XRD spectra reported in Figure 4, where two different peaks can be observed at 20.4 • and 22.7 • for PA11_TL and 20.2 • and 22.8 • for PA11_P40. In the literature, it is reported that the (200) plane of the triclinic α structure appears at 20 • while the (010) and ( 210) planes appear at 23.3-23.5 • [34,35]. Moreover, the (100) plane of the α' structure, which is a pseudohexagonal δ phase, appears at 21 • [36].…”
Section: Dsc and Xrdmentioning
confidence: 99%
“…This is confirmed by the XRD spectra reported in Figure 4, where two different peaks can be observed at 20.4 • and 22.7 • for PA11_TL and 20.2 • and 22.8 • for PA11_P40. In the literature, it is reported that the (200) plane of the triclinic α structure appears at 20 • while the (010) and ( 210) planes appear at 23.3-23.5 • [34,35]. Moreover, the (100) plane of the α' structure, which is a pseudohexagonal δ phase, appears at 21 • [36].…”
Section: Dsc and Xrdmentioning
confidence: 99%
“…The break stress is 2.9 MPa. According to the literature[ 10 , 11 ], TPU containing carbon black will change its mechanical properties, but TPU containing carbon black will have better mechanical properties than TPU without carbon black. The stress-strain curves indicated that the pure TPU could be stretched by up to 160%.…”
Section: Resultsmentioning
confidence: 99%
“…The recent advancements in research and development on polyamide 11 are focused on multi-jet fusion technology, which has enabled the fabrication of functional and convoluted polymeric parts. Multi-jet fusion is a development in polymeric powder bed fusion additive production methods (Tey et al 2021 ). The polyamide 11 polymer powder is used for deposition in the multi-jet fusion fabrication process and sintering of powder occurs when exposed to infrared radiation (Lee et al 2020 ).…”
Section: Bioplastic Precursorsmentioning
confidence: 99%